2016
DOI: 10.1007/s00701-016-2875-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of flow re-direction endoluminal device (FRED) in the treatment of cerebral aneurysms: a single center experience

Abstract: Endovascular treatment with FRED FDD is a safe treatment for unruptured cerebral aneurysms, resulting in a high rate of occlusion. The FRED is substantially equivalent to the other known FDDs, which show similar functions and technical profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Similarly, Möhlenbruch et al 14 showed progressive aneurysmal occlusion with 73% of aneurysms completely occluded at the 6 months' follow-up while Briganti et al 15 had occlusion rates of 83%. The safety profile also seems comparable to the other devices with no deaths seen in the studies and morbidity seen in 10% of cases in the series by Möhlenbruch and 8% in that of Briganti et al 15 The p64 is a braided FDS composed of 64 nitinol wires. Two platinum wires wrapped around the shaft assist in radio-opacity.…”
Section: Introductionsupporting
confidence: 53%
“…Similarly, Möhlenbruch et al 14 showed progressive aneurysmal occlusion with 73% of aneurysms completely occluded at the 6 months' follow-up while Briganti et al 15 had occlusion rates of 83%. The safety profile also seems comparable to the other devices with no deaths seen in the studies and morbidity seen in 10% of cases in the series by Möhlenbruch and 8% in that of Briganti et al 15 The p64 is a braided FDS composed of 64 nitinol wires. Two platinum wires wrapped around the shaft assist in radio-opacity.…”
Section: Introductionsupporting
confidence: 53%
“…1,2,[4][5][6][7][8]10,11,13 In addition, recent cost-effectiveness analyses have favored flow diversion over alternative endovascular treatments, particularly for large or giant aneurysms. 11 However, consensus has not been reached as regards the long-term stability of treatment and complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Due to its singular design, a metal-covered inner stent layer with low permeability and an outer, more porous and stable stent scaffold, the Flow Re-Direction Endoluminal Device (FRED; MicroVention, Tustin, California) may be superior to other flow diverters, providing safer delivery and more effective occlusion of the aneurysm. [4][5][6][7][8][9] The FRED Jr (MicroVention) has a similar dual-layer design and is the first flow diverter dedicated to small vessels (ie, Յ3 mm). In the past, the flow diverter was not widely used in the treatment of distal circulation aneurysms due to their relatively superficial anatomy and good accessibility for microsurgical clipping.…”
mentioning
confidence: 99%